EFEKTIVITAS PENGGUNAAN APLIKASI INTEGRASI PUPUK BERSUBSIDI (IPUBERS) DI DESA SUNGAI ROTAN KECAMATAN RANTAU PANJANG KABUPATEN OGAN ILIR PROVINSI SUMSEL - Muhamad Riki Apriadi; Nurman, Nofi; Yudi Armansyah; Mustiah RH (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the effectiveness of the Integrated Subsidized Fertilizer Application (iPubers) in distributing subsidized fertilizers in Sungai Rotan Village, Rantau Panjang District, Ogan Ilir Regency. iPubers was developed to support targeted, transparent, and accountable fertilizer distribution through digitalized redemption at the kiosk level. This qualitative descriptive study employed observation, in-depth interviews, and documentation involving agricultural officials, extension officers, kiosk managers, and beneficiary farmers. The findings indicate that iPubers is moderately effective in improving transaction transparency, data recording, and distribution monitoring. Nevertheless, effectiveness remains suboptimal due to inaccurate farmer data (NIK discrepancies), limited internet connectivity, technical application issues, and low digital literacy. Supporting factors include government policy support, active extension services, and kiosk commitment. The study concludes that iPubers has strong potential to enhance distribution effectiveness, provided that continuous improvements in data validation, network infrastructure, and user capacity are implemented. Keywords: effectiveness; iPubers; subsidized fertilizer; distribution; digitalization.